Sports, Asia, and the World - EAA Editorial Office (Education About Asia, 2021)
As an eighth-grade junior high graduation present, my parents offered me two options; both Boy Scout-Related: Spend several weeks at the fabled Philmont Ranch (camp) in New Mexico, or travel via train to the Boy Scout Jamboree in Valley Forge Pennsylvania, and then with the troop, to the New York City World’s Fair. Upon examining itineraries, my choice at age thirteen was a no-brainer and had little to do with the afore-mentioned events: The jamboree trip included two New York Mets-Milwaukee Braves baseball games in Shea Stadium; my first live professional baseball attendance chance!
Keywords: American History; Anthropology; Asia General; China; History; India; International Relations; Japan; Singapore; South Korea; United States